2015
DOI: 10.1016/j.fuproc.2014.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic CO2 gasification of a Powder River Basin coal

Abstract: CO 2 gasification of Wyodak low-sulfur sub-bituminous coal from the Powder River Basin (PRB) of Wyoming was conducted in a fixed-bed laboratory gasifier at atmospheric pressure with Na 2 CO 3 , an inexpensive catalyst widely available in Wyoming. The sodium effect on the coal pyrolysis and the sodium forms existing during the char gasification were investigated using thermo-gravimetric analyses (TGA) and X-ray diffraction (XRD) analyses, respectively. Sodium was found to decrease the tar production and promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The yields of both H 2 and CO increase significantly with the increase of pyrolysis temperature. H 2 yield also exhibits a generally increasing trend with increasing loading amount of Na 2 CO 3 when the pyrolysis temperature was kept constant, and the similar conclusion was also drawn in Popa et al and Feng et al's researches [3,28]. Popa et al concluded that the added Na + and the -OH or -COOH groups in coal could react and form -ONa or -COONa, and release H + as presented below [3],…”
Section: Pyrolysis Yield Of Each Gas Component In the High-frequency supporting
confidence: 70%
“…The yields of both H 2 and CO increase significantly with the increase of pyrolysis temperature. H 2 yield also exhibits a generally increasing trend with increasing loading amount of Na 2 CO 3 when the pyrolysis temperature was kept constant, and the similar conclusion was also drawn in Popa et al and Feng et al's researches [3,28]. Popa et al concluded that the added Na + and the -OH or -COOH groups in coal could react and form -ONa or -COONa, and release H + as presented below [3],…”
Section: Pyrolysis Yield Of Each Gas Component In the High-frequency supporting
confidence: 70%
“…Zhang et al [71] studied the interaction of added Na 2 CO 3 and primary minerals in coal gasification, and found that the combination of sodium with either silicon or aluminium changed with carbon conversion and gasification temperatures. Zhang et al [71] studied the interaction of added Na 2 CO 3 and primary minerals in coal gasification, and found that the combination of sodium with either silicon or aluminium changed with carbon conversion and gasification temperatures.…”
Section: Invalidation and Recovery Of Catalystmentioning
confidence: 99%
“…Its generation consists of the formation and rearrangement of free-radical fragments. As reported in previous studies, the formation of tar precursors was hindered by the existence of AAEM metals because of their cross-linking effects. The AAEM metals in treated coal samples were efficiently removed and hydrogen radical was introduced, which are beneficial to the formation and stabilization of free-radical fragments in time during the pyrolysis process.…”
Section: Resultsmentioning
confidence: 54%